NAPQI adducts in patients with selective hypersensitivity to acetaminophen - Gomez-Tabales, Javier; García-Menaya, Jesus M.; Blanca-Lopez, Natalia; Cerezo-Arias, María de las Olas; Silva-Rodríguez, Antonio; Ayuso, Pedro; García-Martín, Elena; Agúndez, José A. G. (Frontiers in Pharmacology, 2026)
IntroductionAcetaminophen, a widely used analgesic and antipyretic, can cause adverse reactions ranging from mild urticaria to severe anaphylaxis. While interindividual differences in pharmacokinetics and genetic polymorphisms are known to affect acetaminophen metabolism, the specific mechanisms underlying hypersensitivity reactions (HSRs) remain unclear.MethodsWe evaluated 28 patients with single-NSAID-induced urticaria/angioedema or anaphylaxis, but no other symptoms after acetaminophen intake. All patients demonstrated selective hypersensitivity to acetaminophen while exhibiting confirmed tolerance to acetylsalicylic acid (ASA). Oral provocation tests were conducted, and NAPQI adducts and acetaminophen metabolites were quantified in serum samples using HPLC coupled with mass spectrometry in these patients and in control individuals.ResultsNAPQI generation occurred early after drug administration, within the timeframe when immediate HSRs occur. NAPQI adducts were 3-fold higher in patients with positive oral provocation compared to patients with negative oral provocation, (P = 0.028), despite lower acetaminophen doses. Detoxified NAPQI metabolites were reduced in HSR individuals, suggesting impaired detoxification. A trend toward higher adduct levels was observed in individuals with GSTM1 null genotypes.ConclusionOur findings indicate that NAPQI adduct generation is closely related to acetaminophen HSRs, supporting a mechanistic link between impaired NAPQI detoxification and acetaminophen HSR. Genetic variability in detoxifying enzymes, particularly GSTM1, may modulate individual susceptibility. These findings warrant further investigation into NAPQI adducts as predictive biomarkers for acetaminophen hypersensitivity.